Gay tourism new perspectives - Vorobjovas-Pinta, Oscar 1987- (Tourism and cultural change, 2021)
"This book examines the emerging and shifting issues in the field of gay tourism, how these relate to significant societal and technological changes and the implications of these changes for theory, policy and practice. It will be a useful resource for students, lecturers and researchers in tourism, human geography, cultural studies and sociology"--